Something old, something new: revisiting the diamondback moth (Lepidoptera: Plutellidae) life table after 65 years. Issue 1 (19th February 2020) - Dancau, Tina; Haye, Tim; Cappuccino, Naomi; Mason, Peter G.
Abstract: Nearly 65 years ago, D.G. Harcourt developed the first of 74 life tables of the diamondback moth, Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae), on the Central Experimental Farm in Ottawa, Ontario, Canada and at nearby sites. This work is cited whenever authors discuss the life history of the diamondback moth and its parasitoids in Canada. Since Harcourt's study, climate change, urbanisation, and crop diversity may have altered the population dynamics of both the diamondback moth and its natural enemy community in the original study area. To follow up on Harcourt's work, we used two approaches to build life tables to describe mortality factors in the field and the natural enemies attacking diamondback moth in Ottawa: destructive sampling of mature cabbage, Brassica oleracea Linnaeus (Brassicaceae), plants similar to Harcourt's approach and a modern sentinel-based approach with an enemy exclusion cage treatment. After 65 years, the primary parasitoids attacking diamondback moth remained the same, although more parasitoid diversity was revealed by the destructive sampling technique. Total mortality and parasitism levels also remained similar. In one notable difference, we attributed more diamondback mortality to predation. Overall, however, diamondback moth population dynamics have changed little in Ottawa in the decades since Harcourt's studies.